2021
DOI: 10.1021/acsami.1c05648
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Nickel–Molybdenum-Based Electrocatalysts for Hydrogen Evolution at Low Overpotentials in a Flow-Through Configuration

Abstract: Three-dimensional (3D) printed, hierarchically porous nickel molybdenum (NiMo) electrocatalysts were synthesized and evaluated in a flow-through configuration for the hydrogen evolution reaction (HER) in 1.0 M KOH­(aq) in a simple electrochemical H-cell. 3D NiMo electrodes possess hierarchically porous structures because of the resol-based aerogel precursor, which generates superporous carbon aerogel as a catalyst support. Relative to a traditional planar electrode configuration, the flow-through configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Remarkably, the use of a resol-based aerogel precursor resulted in the formation of a superporous carbon support, reaching an electrochemical surface area of 25 163 cm 2 . In the aforementioned contribution, Xiang and coworkers also accomplished a study regarding the electrokinetics and the mass transport of the reaction under both flow-through and planar configurations [69].…”
Section: Trends In Chemistrymentioning
confidence: 99%
“…Remarkably, the use of a resol-based aerogel precursor resulted in the formation of a superporous carbon support, reaching an electrochemical surface area of 25 163 cm 2 . In the aforementioned contribution, Xiang and coworkers also accomplished a study regarding the electrokinetics and the mass transport of the reaction under both flow-through and planar configurations [69].…”
Section: Trends In Chemistrymentioning
confidence: 99%
“…[91] Recently, 3D-printed lattice structures with open large low-tortuous channels have been developed for tackling bubble migration. [31,92,93] Kou et al showed that a 3D-printed Ni lattice electrode with high surface area and low-tortuous channels can mitigate gas bubble traffic during alkaline water electrolysis at high current densities (Figure 17a). [31] The periodic porous electrode allows rapid bubble movement and releasing, achieving low HER (245 mV) and OER (425 mV) overpotentials at the ultrahigh current density of 1000 mA cm À2 , respectively.…”
Section: Lattice Structures: Facilitating Bubble Transportmentioning
confidence: 99%
“…OER 425 mV @ 1000 mA cm À2 NiMo HER 1.0 M KOH aq. 45 mV @ 10 mA cm À2 24 h @ 10 mA cm À2 [92] Stainless steel OER 1.0 M KOH with 0.6 M NaCl aq.…”
Section: Patterned Structures: Achieving Uniform Flow-field Distribut...mentioning
confidence: 99%
“…Rational three-dimensional (3D) structure at a macrolevel can optimize the bubble transport path and suppress the severe bubble coalescence in the local structure to enable the full exploitation of the intrinsic activity of the catalyst. It is supposed to be a promising path to further promote the mass transfer under industrial-scale high hydrogen evolution rate but is often overlooked due to the constrained choice of 3D substrates, such as Ni foam and Ti mesh. However, even for the state-of-the-art 3D structures, the specific surface area exhibits a “seesaw” relationship with the bubble transport capacity since the larger specific surface area tends to have more complex structures with small pore sizes. , For example, for commercial nickel foam (NF), the most common 3D substrate, although its porous structure leads to increased active sites, its mass transport ability is seriously limited by the bubble trapping caused by the randomly oriented pores throughout the structure . This means that the structural design of 3D catalysts under different conditions requires a focus between the chemical reaction zone and mass transfer; therefore, rational 3D structures of monolithic catalysts are urgently needed to balance the structural influence factors for maximizing performance, but the related studies have never been reported.…”
Section: Introductionmentioning
confidence: 99%